Hypochlorite Leaching Of Gold Ore - Mohamad Zaidi, Mohamad Za'im (Universiti Sains Malaysia, 2018)
In this research project, the bulk gold ore sample received from Kuala Lipis, Pahang was used. The gold ore was first sieved to determine the particle size distribution of the gold ore sample. Result from sieving shows that only 11.20 % of the gold ore sample is -75 µm. The bulk gold ore sample then was ground to obtain 80 % of the sample passing -75 µm. Before conducting the hypochlorite leaching with two different parameters which is the temperature and concentration of calcium hypochlorite [Ca(OCl)2], the sample undergoes characterization and mineralogical study. The study was done to determine the chemical composition, major phases presence, and the elements that associated with the gold ore sample using XRF, XRD, SEM and EDX. From XRF, XRD, SEM and EDX analysis, it was found that distribution of gold is partly arsenopyrite (FeAsS) and quartz. The gold content in the gold ore sample is 6.91 g/t which was obtained from assaying method. BLEG method was used to determine the free milling gold which is 4.58 g/t. From the comparison of the percentage of gold leached between the variables which is temperature at 45 °C and 55 °C and the concentration of calcium hypochlorite which is 0.25 M and 0.75 M, the best condition to conduct hypochlorite leaching was using 0.75 M of calcium hypochlorite at ambient temperature, 27 °C. This condition gave the highest percentage of gold leached with 72.20%.